ANALISIS DAMPAK EKONOMI PENUTUPAN KAWASAN LOKALISASI KOTA SURABAYA ( Studi Deskriptif Dampak Ekonomi Penutupan Lokalisasi Dolly bagi masyarakat di Kelurahan Putat Jaya Kota Surabaya ) - Dedi Isnandar (Faculty of Social and Political Science, 2015)
This research is the economic impact of the closure of Dolly the city of Surabaya. This study takes the title: